Anti-inflammatory and antibacterial activity study of some novel quinazolinones - R. Nanthakumar; P. Muthumani; K. Girija (Arabian Journal of Chemistry, 2014)
Anti-inflammatory and antibacterial activities of some novel quinazolinones were determined. Evaluation of anti-inflammatory activity of test compounds was performed using carrageenan induced paw edema in rats. Oral administration of test compounds 25 mg/kg and 50 mg/kg reduced the paw edema significantly (P < 0.05) in a dose dependent manner compared to carrageenan induced rats. The test compounds were also screened for their antibacterial activity against the strains of Staphylococcus aureus and Escherichia coli at the concentrations of 200 μg/ml and 1 mg/ml. The test compounds showed better activity as that of the standard lincomycin at the tested higher concentration against S. aureus. None of the compounds exhibit comparable activity to that of the standard ceftazidime against E. coli.